Islamic financial development and economic growth-empirical evidence from United Arab Emirates / Mosab I. Tabash and Raj S. Dhankar - Dhankar, Raj S. (Faculty of Business and Management, 2014)
This paper analyzes empirically the relationship between the development of Islamic finance system and growth of the economy in the United Arab Emirates (UAE). To document the relationship between development of Islamic finance and economic growth, time series data from 1990 to 2010 were used. We use Islamic banks’ financing credited to private sector through modes of financing as a proxy for the development of Islamic finance system and Gross Domestic Product (GDP), Gross Fixed Capital Formation (GFCF), as proxies for real economic growth. For the analysis, the unit root test, cointegration test and Granger Causality tests were done. Our empirical results show that there is a strong positive association between Islamic banks’ financing and economic growth in the UAE, which reinforces the idea that a well-functioning banking system promotes economic growth. However, our results indicate that a causal relationship happens only in one direction, i.e., from Islamic banks’ financing to economic growth, which supports Schumpeter’s supply-leading theory. In this case, the development in the Islamic financial sector acts as supply, leading to transfer of resources from the traditional, low-growth sectors to the modern high-growth sectors, and to promote and stimulate an entrepreneurial response in these modern sectors. Furthermore, the results show that Islamic Banks’ financing has contributed to the increase of investment in UAE in the long term and in a positive way.